Research on translations of tests: Validation of the spanish version of the young adult alcohol consequences questionnaire (S-YAACQ) - Pilatti, Angelina (2015)
The present work was aimed at analyzing the psychometric properties of a Spanish version of the 48-item Young Adult Alcohol Consequences Questionnaire (YAACQ) by applying the item response theory. Participants were 247 college students (75.7% female) who reported drinking alcohol within the last 3 months. The 48-item YAACQ was translated into Spanish and back to English. The psychometric properties of the Spanish YAACQ (S-YAACQ) were analyzed applying the Rasch model, as well as group difference and correlational analyses. Factor structure of the S-YAACQ was analyzed using confirmatory factor analysis. The verification of the global fit of the data showed adequate indexes for persons and items. The reliability estimates for the items and the persons were both high. Scores on the S-YAACQ were strongly correlated with scores on the Spanish versions of the AUDIT and the RAPI and with frequency of binge drinking. Five of 48 items showed different item functioning (DIF) as a function of gender. These biases were in opposite directions, resulting in DIF cancellation. The item severity continuum was largely similar to that found with the Spanish brief YAACQ and to that found in U.S. and Dutch samples. Overall, results from the present study suggest that this translated full version is better suited than the brief YAACQ for the identification of youth who are experiencing problems with alcohol. Findings suggest that the Spanish version of the full YAACQ may be used to identify a broad diversity of alcohol-related problems in Spanish-speaking college students.